Evaluation of fecal sample collection methods for feline gut microbiome profiling: fecal loop vs. litter box - Ma, Xiaolei; Brinker, Emily; Lea, Christopher R.; Delmain, Diane; Chamorro, Erin D.; Martin, Douglas R.; Graff, Emily C.; Wang, Xu (Frontiers in Microbiology, 2024)
Microbial population structures within fecal samples are vital for disease screening, diagnosis, and gut microbiome research. The two primary methods for collecting feline fecal samples are: 1) using a fecal loop, which retrieves a rectal sample using a small, looped instrument, and 2) using the litter box, which collects stool directly from the litter. Each method has its own advantages and disadvantages and is suitable for different research objectives. In this study, we aimed to evaluate the influence of collection methods on feline microbiome analysis, particularly their impact on DNA extraction, metagenomic sequencing yield, microbial composition, and diversity in subsequent gut microbiome analyses. Whole-genome shotgun metagenomic sequencing was performed on the gut microbiomes of fecal samples collected using these two methods from ten adult cats housed in the same research facility. Fecal sample collection using a fecal loop resulted in a lower yield of microbial DNA compared to the litterbox method (P = 0.004). However, there were no significant differences between the two groups in the proportion of host contamination (P = 0.106), virus contamination (P = 0.232), relative taxonomy abundance of top five phyla (Padj > 0.638), or the number of microbial genes covered (P = 0.770). Furthermore, we did not observe significant differences in alpha-diversity, beta-diversity, the number of taxa identified at each taxonomic level, and the relative abundance of taxonomic units. Taken together, these results indicate that collecting fecal samples directly from the litterbox within six hours after defecation can be considered a reliable approach for microbiome research.